Transcatheter Arterial Chemoembolization in Combination With High-Intensity Focused Ultrasound for Intermediate and Advanced Hepatocellular Carcinoma: A Meta-Analysis - Wang, Yun-Bing; Ma, Rong; Wang, Zhi-Biao; Shi, Qiu-Ling; Zhang, Lian; Chen, Wen-Zhi; Gong, Jian-Ping; Bai, Jin (Frontiers in Oncology, 2022)
Background The study was conducted to explore whether high-intensity focused ultrasound (HIFU) can improve the effect of transcatheter arterial chemoembolization (TACE) in intermediate and advanced hepatocellular carcinoma (HCC). Methods PubMed, Embase, Cochrane Library, Web of Science, Wanfang Data, CQVIP, China National Knowledge Infrastructure (CNKI), and Chinese Biomedical (CBM) databases were searched for randomized controlled trials (RCTs) comparing the effect of TACE in combination with HIFU group (group A) to TACE alone group (group B) in treating intermediate and advanced HCC. The primary outcomes were overall survival (OS) rate and tumor response rate. The odds ratio (OR) and 95% confidence interval (CI) for each study were calculated and then pooled with fixed effects model or random effects model. Sensitivity analyses and subgroup analyses were conducted. A publication bias was also evaluated. Results After literature selection, eleven RCTs involving 803 patients were included in this meta-analysis. This meta-analysis revealed that group A was associated with an increased 6-month OS rate (OR = 0.20), 12-month OS rate (OR = 0.23), 24-month OS rate (OR = 0.32), and overall response rate (WHO criterion, OR = 0.22; RECIST criterion, OR = 0.30). Furthermore, subgroup analyses showed no bias in the result. Given the limited number of studies that reported major complications, no additional meta-analysis of complication was conducted. Despite no special treatment, any complication following HIFU treatment was found to subside within 3-7 days. Conclusion TACE in combination with HIFU is associated with increased OS and tumor response in intermediate and advanced HCC. Current evidence supports the use of HIFU after TACE treatment in intermediate and advanced HCC.